Student usage of open educational resources and social media at a Sri Lanka Medical School - Hettige, S.; Dasanayaka, E.; Ediriweera, D.S. (BioMed Central, London, 2022)
Background: The use of Open Educational Resources (OER) and Social Media (SM) for academic information seeking is common among undergraduates nowadays. There is limited data on OER and SM use for education in Sri Lanka. This study was aimed at evaluating the OER and SM use for education among the medical students at the Faculty of Medicine, University of Kelaniya, Sri Lanka. Methods: A cross-sectional study was conducted at the Faculty of Medicine, University of Kelaniya. Stratified random sampling was used to select students from the first year to the final year. A self-administrated questionnaire was used to collect data. Results: The study included 257 responses (response rate: 89.5%), of which 185 (72.0%) were females. The OER and SM use for educational purposes at least once a month among students was 96.1% (95%CI: 93.7-98.5%) and 88.3% (95%CI: 84.4-92.3%) respectively. There was no gender difference in OER and SM use. The main reasons for accessing OER were the availability of information at any time (36.1%) and ease of information access (31.5%). Wiki sites (84.4%) and Facebook (79.8%) were the highest accessed OER and SM platforms. The majority of students were in view that the information on wiki sites (51.4%) and results of general non-specific web searches (56.0%) were reliable. Only 33.9% of students searched information from educational and government-related sources and 18.7% had accessed e-journals. Through SM, 79.0% joined educational groups and 77.0% followed the medical-related sites, pages and people. More than one-third of students (35.8%) could not find academic information from SM due to the information overload and 31.1% mentioned that SM distracted their education. Conclusion: The majority of the students used OER and SM for education; however, only a minority accessed reliable information. Students accepted information available in wiki sites and general non-specific web searchers without considering the credibility of sources. The majority of the students did not refer to e-journals. Distractions to academic work and the difficulty to access accurate information were major concerns of using SM. This study highlights the importance of improving information literacy among medical students.
Indexed in MEDLINE.
Keywords: Academic information seeking; Facebook; Free educational resources; Medical students; Open educational resources